The Effect Of Symbolic Modeling Techniques on High School Students’ Altruistic Behavior - Elma Rusita Dewi; Wan Alawee Samaeng; Suci Prasasti; Erik Teguh Prakoso (Program Studi BKPI IAIN Salatiga, 2023)
The purpose of this study was to determine the effect of group counseling service with symbolic modeling technique on the altruistic behavior of class XI students at SMA Muhammadiyah 1 Sragen in the 2022/2023 academic year. To this end, a pre-experimental study with one group research pre-test and post-test was applied. Participants were ten 11th-grade students in Natural Science and Social Science Departments. Data were collected using questionnaires, interviews, observation, and documentation. Data analysis with paired sample t-test by paired sample t-test, showing t-count of 5.000, which was higher than the t-table (1.833) with a significance value of 0.001 ( 0.05). The comparison value of the pre-test and post-test showed a score of 11.20. To sum up, the pretest and posttest results demonstrated that group guidance with symbolic modeling techniques enhanced the altruistic behavior of class XI students at SMA Muhammadiyah 1 Sragen during the 2022/2023 Academic Year